Pathological knee laxity in elite women team handball players: a pilot study - L’Hermette, Maxime; Coquart, Jeremy; Senioris, Antoine; Chamari, Karim; Tourny, Claire; Dujardin, Franck (Biology of Sport, 2018)
To identify the anterior cruciate ligament (ACL) laxity thresholds and to evaluate the utility of this measure in case of onset of knee injury for elite women handball players. Anterior laxity was measured by an arthrometer. Data on 29 elite women handball players and 20 sedentary women were collected. Among the handball group, 9 participants suffered from full-thickness ACL tears. The recorded variables were the anterior knee laxities at pressure load (PL) of 134 N (PL134N) and 250 N (PL250N) on the upper calf, which allowed assessment of the inter-leg comparison by calculating the differential laxity thresholds and the differential slope coefficients. Considering the healthy knee as a reference within the injured players, the laxity thresholds were identified, and the diagnostic value of the tests was assessed. The handball players without a full-thickness tear presented lower knee laxity than the sedentary women, and 75% were diagnosed with pathologic laxity in at least one of the knee joints, compared to 10% of sedentary women. The differential laxity threshold was identified between the handball players without a full-thickness tear and those with a full-thickness tear at 1.5 mm with PL134N and 2.2 mm with PL250N. The best diagnostic result was obtained using PL250N (area under the curve = 0.95). Handball practice is associated with specific laxities that are rarely seen in the general population. The ACL laxity thresholds may be useful measures to check the state of the ACL and to suggest full-thickness tears, as joint laxity appears to be a factor contributing to ACL tears in female handball players.